Audit Information System Development using COBIT 5 Framework (case Study: STMIK STIKOM Bali) - Budiarta, Komang; Iskandar, Adi Panca Saputra; Sudarma, Made (International Journal of Engineering and Emerging Technology; Vol 1 No 1 (2016): July - December, 2017)
Information technology (IT) is a very important part for the company or institution and investment value to make the company or institution for the better. Companies or institutions using information technology to  make the support of the strategic plan company in Attaining the vision, mission and objectives of the company or the institution, as well as STMIK STIKOM Bali. Applied information technology in the companies or institute need to be regulated. Managing information technology requires an audit for evaluating and ensure compliance in terms of the standard approach. Information Technology in Bali STIKOM STMIK require audits to evaluate, assess capabilities and make a recommendation for manage information technology better. Framework COBIT 5 is use for audit, that focuses on the purpose IT service delivery in accordance with business needs. The results of audit use framework COBIT 5 with 17 process capability obtained is 2.66, which states that the implementation of IT services is already established and has a standard.